(untitled) (Journal of Pathology of Nepal, 2011)
Background: Helicobacter pylori infection is associated with mixed inflammatory cell infiltrate consisting of neutrophils, eosinophils, lymphocytes and plasma cells. Helicobacter pylori lead to mast cell degranulation and release of active chemical compounds in in-vitro conditions. The objective of this study was to find out the association of mast cell density and Helicobacter pylori in the antral mucosa of the stomach. Materials and Methods: A total of 150 endoscopic biopsies were included in the study. In addition to routine Hematoxylin and Eosin stained slides, Giemsa stain was done in each case for the evaluation of Helicobacter pylori and mast cell density in the gastric mucosa. Results: Out of 150 gastric biopsies with histopathological diagnosis of chronic gastritis, 36 cases (24%) were positive for Helicobacter pylori. In the antral mucosa, mast cell density was significantly higher in the Helicobacter pylori-positive group than in the Helicobacter pylori-negative group (P<0.01). Conclusion: Mast cells may play a role in the development of Helicobacter pylori gastritis. Keywords: Gastritis; Mast Cell; Helicobacter pylori DOI: 10.3126/jpn.v1i1.4448 Journal of Pathology of Nepal (2011) Vol.1, 34-36